Hemoglobin-Crosslinked Polyacrylamid Hydrogels: Swelling Behaviour Analysis - Bajpai, S.K. (Asian Journal of Chemistry, 2010)
Hydrogels have been prepared by polymerizing and crosslinkingacrylamide in the alkaline solution of hemoglobin. The swellingbehaviour of hemoglobin-crosslinked polyacrylamide hydro gelswas analyzed in water and in citric acid-phospate buffer solutionsat various pH. The effect of temperature on the swelling behaviourwas also analyzed by varying the temperature from 25 to 60°C.Amount of crosslinking agent also affected the swelling capacity.Swelling parameters such as penetration velocity and diffusion coefficientwere also evaluated. The gels were found to show reversibleswelling and deswelling processes.